DESIGNING PROTOCOLS FOR ABDUCTIVE HYPOTHESIS REFINEMENT IN DYNAMIC MULTIAGENT ENVIRONMENTS. (11th September 2012) - Bourgne, Gauvain; Maudet, Nicolas
<x xml:space="preserve">Abstract</x> This paper studies multiagent systems where each agent has access to local observations of a dynamic environment and needs to build from this partial information an hypothesis on the state of the system. Each agent ensures that its hypothesis is consistent with its observations, and communicates with other agents to refine this hypothesis by confronting them to their own views. However, these communications are restricted by temporal and topological constraints, and can only be bilateral. We first study in this paper an abstract model of this problem, identifying conditions under which satisfying states can (or will) be reached. We rely in particular on a compositional consistency relation. We then detail a case study involving agents able to reason abductively (with Theorist), and study how demanding are the conditions required in this context. Different bilateral protocols are finally introduced and formally studied, to account for both compositional and noncompositional settings.